Sociodemographic, medical, health behavior, and psychosocial factors associated with COVID-19 diagnoses in the New Jersey cancer survivor cohort - Sharon Manne; Adana A. M. Llanos; Hari S. Iyer; Lisa E. Paddock; Katie Devine; Shawna V. Hudson; Denalee O’Malley; Elisa V. Bandera; Sara Frederick; Jacintha Peram; Justin Solleder; Shengguo Li; et al. (Cancer Causes & Control, 2025)
Background Cancer survivors are more susceptible to contracting COVID-19. However, beyond race, age, and sex, less is known about other neighborhood and psychosocial factors contribute to this increased risk. Objective The goal of this study was to examine the associations of individual and area-level social determinants of health (SDOH) measures, medical, lifestyle, and psychosocial factors and COVID-19 infection in a statewide cohort of cancer survivors in New Jersey. Methods Survey data from 864 cancer survivors in New Jersey were collected from 2018 to 2022, which were merged with study participant data from the state of New Jersey on COVID-19 diagnoses in 2020, 2021, and 2022. We estimated adjusted odds ratios (aOR) for associations of COVID-19 diagnosis with individual-level factors (cancer type and stage, health behaviors, and psychosocial factors) and area-level SDOH [Social Vulnerability Index, Area Deprivation Index, and Index of Concentration at the Extremes (ICE) to quantify racialized deprivation vs. privilege based on income]. Results Cancer survivors born outside the US were more than twice as likely to contract COVID-19 compared to US-born survivors (aOR 2.29, 95% CI 1.01, 4.92). Compared to Quartile 4, residence in an area in Quartile 1 of racialized income ICE (i.e., predominantly Black, low income) was associated with higher odds of COVID-19 (aOR 2.15, 95% CI 0.98, 4.87). Retired survivors had lower odds of COVID-19 (aOR 0.39, 95% CI 0.19, 0.80) compared to those who were employed. Higher social well-being was associated with higher COVID-19 (aOR 1.07, 95% CI 1.02, 1.13). Type of cancer and cancer treatments received were not associated with the risk of COVID-19. Conclusions Immigrant status and increased racialized deprivation as measured by ICE for income were associated with COVID-19. These findings support evidence that individual and area-level SDOH measures contribute to increased risk of COVID-19 among cancer survivors.

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)